A framework for the provision of flexibility services at the transmission and distribution levels through aggregator companies. (March 2019) - Lampropoulos, Ioannis; Alskaif, Tarek; Blom, Jelle; van Sark, Wilfried
Abstract: A hierarchical control framework is proposed that enables the provision of flexibility services in power systems through aggregation entities. The focus is on both wholesale energy trade functions, i.e. day-ahead market optimisation, and ancillary services to the operators of the transmission and distribution systems, i.e. provision of automatic frequency restoration reserves and peak shaving services. The control framework is generic, scalable, and is effectively configured to address all those diverse needs originating from the lower level, i.e. the device or the user, to the distribution and transmission levels. The work includes the establishment of procedures to identify and solve possible conflicts between the operators of the transmission and distribution systems when procuring ancillary services with competing objectives. The framework is applied on a case study focusing on an aggregation of residential buildings in the Netherlands which are equipped with photovoltaic installations and battery-based energy storage systems. The annual costs and benefits are calculated by using historical market data, whereas the simulation scenarios address the impact of different levels of generation and demand forecasting errors in the economic performance. The outcome of computer simulations provides an informative insight into the differences between the strategies of aggregator companies, and the potential of the investigated markets. The economic evaluation includes the value estimation of peak shaving services at the distribution level. An increase in procurement costs for such services is expected to stimulate the distribution system operators to invest into grid capacity enhancement.